2022
DOI: 10.3389/fnhum.2022.905837
|View full text |Cite
|
Sign up to set email alerts
|

Rhythms of human attention and memory: An embedded process perspective

Abstract: It remains a dogma in cognitive neuroscience to separate human attention and memory into distinct modules and processes. Here we propose that brain rhythms reflect the embedded nature of these processes in the human brain, as evident from their shared neural signatures: gamma oscillations (30–90 Hz) reflect sensory information processing and activated neural representations (memory items). The theta rhythm (3–8 Hz) is a pacemaker of explicit control processes (central executive), structuring neural information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 197 publications
0
16
0
1
Order By: Relevance
“…The higher theta and gamma oscillations conceivably indicated more active attention events occurred during awake. 28 , 29 By contrast, BKO monkeys showed peaked alpha and beta power at near 8 Hz and 15–30 Hz bands, respectively, in both day and night periods ( Figures 2 C and S2 B). Of note, by summarizing 24-h EEG spectra of the three WT and BKO monkey pairs, we found that beta and gamma powers were higher in BKO than in WT monkeys ( Figure 2 D) and appeared in all stages, including awake, REM, N1/N2, SWS ( Figure S3 A).…”
Section: Resultsmentioning
confidence: 95%
“…The higher theta and gamma oscillations conceivably indicated more active attention events occurred during awake. 28 , 29 By contrast, BKO monkeys showed peaked alpha and beta power at near 8 Hz and 15–30 Hz bands, respectively, in both day and night periods ( Figures 2 C and S2 B). Of note, by summarizing 24-h EEG spectra of the three WT and BKO monkey pairs, we found that beta and gamma powers were higher in BKO than in WT monkeys ( Figure 2 D) and appeared in all stages, including awake, REM, N1/N2, SWS ( Figure S3 A).…”
Section: Resultsmentioning
confidence: 95%
“…Recent research has revealed a significant relationship between theta-gamma PAC and information processing in working memory, as demonstrated by various studies [3336]. Both theta and gamma bands have separate functions in cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect includes regulating the timing and synchronization of neural activity, facilitating transitions between distinct information-processing tasks, encoding and retrieving memories, updating language, engaging in predictive processing, and organizing memory [33]. In tasks related to information organization, theta-gamma PAC plays a crucial role by enabling specific information to be activated or reactivated at specific times for facilitating information-processing adjustments [33, 36, 41]. A theta-gamma PAC is involved in attention-selection mechanisms, which reduce interference from other information sources and support a focus on specific information [42].…”
Section: Introductionmentioning
confidence: 99%
“…30–90 Hz) has numerous significant functions in human cognition. Its synchronization is associated with the integration of perceptual features in bottom-up processes driving object representation, as well as with attentional and mnemonic top-down processes (Köster and Gruber 2022 ). The maintenance of mental representations in working memory as well as successful encoding and retrieval of long-term memory relies on the gammaband’s synchronization (Jensen et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%